Nilai-Nilai Pendidikan Kesetaraan Gender dan Pemberdayaan Perempuan dalam Tradisi Jawa - Raikhan Raikhan (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2023)
This research aims to identify and analyze the educational values of gender equality and women's empowerment in the Javanese tradition through a biblical-critical study. This qualitative research method analyzes various written sources such as traditional books, scientific articles, and local literature using thematic content analysis, critical interpretation with the lens of cultural feminism and Javanese emic perspectives, and cultural hermeneutics. The results of the study show that Javanese traditions contain the value of appreciation for the role of women in rituals, the representation of female figures as symbols of empowerment (agency, autonomy, leadership), as well as social values such as mutual cooperation, manners, and flexibility that have the potential to support the harmony of gender relations. The conclusion of the study confirms that the noble values in the Javanese tradition are relevant to be integrated in modern education through cultural recontextualization. The contribution of this research lies in the identification of specific values in the Javanese tradition that can enrich the local culture-based education curriculum that is gender-responsive.